PENGARUH PENDEKATAN HUMAN RELATIONS TERHADAP KINERJA PEGAWAI (Suatu Studi Pada Badan Kepegawaian Daerah Kabupaten Halmahera Barat) - Bethol, Iwan Christian; Kiyai, Burhanuddin; Kolondam, Helly (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstrak: The research was conducted on the basis of initial observations location study indicated thatemployee performance is still relatively low. The relatively low performance of employees is presumablyrelated to the implementation of human relations factors in the work environment at the RegionalEmployment Board of West Halmahera. Thus, this study aims to: (1) to investigate the implementation ofhuman relations approach. (2) To determine the achievement of employee performance. (3) To analyze theeffect of the implementation of human relations approach to employee performance at the RegionalEmployment Board West Halmahera district. By applying the method of descriptive and quantitativeapproach, respondents were determined purposively sampled as many as 53 employees, then distributed alist of questions or the questionnaire, the results are tabulated and analyzed by applying statisticaltechniques. To describe the research variables used analytical technique that is processed in the percentageof Frequency Distribution Table, while to test the hypothesis used a simple linear regression analysis andcorrelation of product moment.Once the data is collected and then analyzed the results showed that (1) Implementation of human relationsapproach in working condition at the Regional Personnel Agency (BKD) West Halmahera has succeededin improving the performance of employees that are in the category of "high". (2) The increasedperformance of employees at local staffing agency West Halmahera succession is determined or influencedby the application of human relations approach in working condition.Thus, it can be concluded that the hypothesis which states that "the human relations approach effect onEmployee Performance in the Regional Employment Board of West Halmahera District", acceptableempirically at the same time justifying the underlying theories. Can be given some suggestions as follows:(1) To optimize employee performance, it is recommended to local governments West Halmahera streamlineperformance benefits are selective and controlled in order to avoid wastage of financial areas, as well asboost employee performance itself. (2) In addition, the application of human relations approach is neededmore fused with a bureaucratic culture that is based on the culture and local wisdom to better work togetherin encouraging employee performance more optimally.Keywords: Approach Human Relations, Employee Performance